Preliminary assessment of adaptability of Leningrad-Zagreb Mumps vaccine virus to human diploid cells and vero cells. - RAVINDRA MULE; RAJEEV DHERE (International Journal of Pharma and Bio Sciences, 2017)
Mumps is a highly contagious childhood respiratory disease preventable by vaccination. Leningrad-Zagreb (L-Z) strain based mumps vaccine is one of the safe and effective vaccines, being used for successful immunization in many countries. It is being produced on the primary culture of chicken embryo fibroblast. This culture needs to be initiated using specific pathogen free (SPF) eggs, derived from SPF flocks of chickens. Primary cultures prepared from the avian source have inherent limitations such as variations in the supply of eggs and the potential risk of adventitious agents escaping possibility of detection. Above mentioned limitations could be overcome by using well characterized banks of cell substrates to grow the virus. MRC-5 cells and Vero cells formed excellent alternative cell substrates to assess the adaptability of the L-Z mumps virus. These banked cell substrates offer distinct advantages in vaccine production technology because of their ready availability, well characterized attributes such as homogeneity, stability, purity, identity, faster growth rates and consistent supply. Successful adaptation of the L-Z mumps vaccine virus to these cell substrates could therefore be translated into shortened cycle times and improved productivities, thus benefiting the vaccine industry and society at large.This report describes the preliminary assessment of adaptability of the L-Z mumps vaccine virus to the human diploid cell strain, MRC-5 and the Vero cell line in comparison with it’s original cell substrate. The original CEC-grown L-Z mumps virus was consecutively passaged for few times through MRC-5 cells and Vero cells in two different sets of experiments. Adaptability of the passaged viruses was qualitatively checked by mumps-specific immune-fluorescence assay. It was also quantitatively assessed by performing the standard tissue culture infectivity dose titration. Adaptability of the original L-Z mumps virus to Vero cells was observed to be much better than that to MRC-5 cells.